The Master of Public Health (MPH) Program at the School of Public Health, Tehran University of Medical Sciences, Iran - A Mesdaghinia; H Keshavarz; A Djazayery; S Nedjat; A Salehi (Tehran University of Medical Sciences, 2009)
"nThe main aim of the Master of Public Health (MPH) program is to equip the participants with the knowledge and skills essential for better service management and applied (including health system) research. The content of the program is revised and expanded in the last three decades and currently there are different MPH programs included the general MPH, Modular MPH, Medical Ethics MPH and MD-MPH programs. General evaluation and feedback show that the MPH program has been reasonably successful.  MPH program enables participants to perform their duties and functions more successfully.